The Impact of Population Growth Rate, Minimum Wage, and Education on The Unemployment Rate in 2022 - Mahdali, Amelia (Jambura Equilibrium Journal, 2024)
Increasing living standards is the main goal of economic development. Unfortunately, the government does not appear to be concerned about the current unemployment issue. The unemployment rate is typically correlated with population growth and is not reinforced by the availability of new jobs; employers' unwillingness to create jobs for them means finding or creating jobs is impossible. Conversely, low levels of education can raise unemployment because it will be harder to find an appropriate job without expertise or knowledge. On the other hand, living an acceptable life and earning an adequate income will improve life quality. This research aimed to examine the relationship between rates of unemployment and the rate of population growth, the minimum wage, and the typical duration of schooling. Secondary data from 2022 was used in this investigation. The research applied double regression analysis with SPSS version 22 as the analytical tool. Based on the analysis's findings, migration, birth rate, and death rates were the main influencing factors, with a significant rate of 0.793>Î±=0,005 indicating that the population growth rate did not affect the unemployment rate. The minimum wage had a long-term effect rather than a direct one during the year, even though it had no obvious impact on the unemployment rate of 0.189>Î±=0.05. The data showed that, even though the typical duration of schooling rises annually, the unemployment rate is significantly influenced by it (0.001